spy force mission: The nightmare vortex - Abela, Deborah; George O'Connor (New York An imprint of Simon & schuster Chilldren's Publishing Division, 2023)
On the outside max Remy look like every other eleven year old, but don't be fooled. Now official members of Spy force, Max and her best friend, linden, are invited to the annual Spy awards, hidden on a secret island deep within a medieval fortress. But then the evil Mr. Blue intercepts Spy force intelligence and discovers the location of the top secret ceremony, and he plots to bring a dormant volcano to life. Max and Linden have only hours to save the spy agency and the world. are they up to the task?
english